Functional characterization of a conserved pair of NKR‐P1 receptors expressed by NK cells and T lymphocytes in liver and gut. Issue 2 (4th December 2014) - Kveberg, Lise; Sudworth, Amanda; Todros‐Dawda, Izabela; Inngjerdingen, Marit; Vaage, John T.
<x xml:space="preserve">Abstract</x> Natural killer cell receptor protein 1 (NKR‐P1) molecules are C‐type lectin‐like receptors modulating cellular responses toward target cells expressing C‐type lectin‐like related (Clr) molecules. Although the function of the prototypic rat NKR‐P1A receptor and its inhibitory counterpart NKR‐P1B are known, little is known about NKR‐P1F and NKR‐P1G apart from their promiscuity for Clr ligands. Here we generated mAbs against both receptors for phenotypic and functional analyses in rat tissues. NKR‐P1F induced redirected lysis and robust Ca2+ signaling in NK cells, which were prevented by simultaneous engagement of NKR‐P1G. NKR‐P1G also inhibited NK‐cell lysis of Clr transfectants. NKR‐P1F was expressed by most NK cells and NKR‐P1A+ T cells in all tissues analyzed, and by many NKR‐P1A− intestinal T cells, while NKR‐P1G was expressed by subsets of these cells with highest prevalence in gut and liver. In the intraepithelial compartment, the proportion of NKR‐P1A+ and NKR‐P1F+ cells was high at birth and thereafter declined, while NKR‐P1B+ and NKR‐P1G+ cells increased with age. Expression levels were also modulated by cytokines, with an increase of NKR‐P1B and NKR‐P1G induced by inflammatory cytokines, and a reduction of NKR‐P1A by TGF‐β. The physiological impact of NKR‐P1 receptors might thus be dependent on age, tissue, and inflammatory status.